Faktor-Faktor Penentu Eksistensi Penjual Pinang di Kabupaten Manokwari (Studi Kasus Distrik Manokwari Barat) - Mus Mualim; Maria M. Semet (JFRES Journal of Fiscal and Regional Economy Studies, 2018)
This study attempted to analyze the causal relationship between a number of factors that were thought to be determinants of the existence of betel sellers in the West Manokwari District. These factors are the attraction of income, employment pressure, and family factors. these three factors are also internal components that are inherent in the profile of pinang sellers in West Manokwari District. Respondents of this study amounted to 96 people selling betel nut in Manokwari.Using multiple linear regression analysis, the results of this study indicate that the biggest factor determining the existence of areca nut seller in Manokwari Regency is a family factor. This illustrates that the choice of betel sellers to stay in small businesses selling betel nuts in Manokwari is more dominant due to family factors.